Malacoplakia of the Uterine Cervix: A Case Report - Adela Saco; Natalia Rakislova; Lorena Marimon; Aureli Torne; Berta Diaz-Feijoo; Rafael Salvador; Silvia Alos; Dercio Jordao; Juan Carlos Hurtado; Jaume Ordi (Pathogens, 2021)
Malacoplakia is an uncommon chronic granulomatous inflammation that rarely affects the female genital tract. A case of a 78-year-old woman with malacoplakia involving the uterine cervix and the vagina is described. The patient complained of vaginal bleeding. Clinically, a 13-mm mass was detected in the cervix, which was confirmed by ultrasound scan and magnetic resonance imaging. Histological examination showed a dense histiocytic infiltrate with abundant Michaelis–Gutmann bodies involving the uterine cervix and the upper vagina. The presence of Escherichia coli was confirmed in the lesion by immunohistochemistry and polymerase chain reaction. Only 12 cases of cervical malacoplakia have been reported to date. This condition should be included in the differential diagnosis of cervical tumors.